Health screening disparities in people living with HIV; A nationwide organized screening setting - Boyoung Park; Yoonyoung Jang; Taehwa Kim; Yunsu Choi; Kyoung Hwan Ahn; Jung Ho Kim; Hye Seong; Youn Jeong Kim; Jun Yong Choi; Joon Young Song; Shin-Woo Kim; Sang Il Kim (Elsevier, 2024)
Background: We identified the uptake of people living with HIV (PLWH) using health-screening services and compared the screening rate with the general population, to identify factors associated with the use of screening services by PLWH. Methods: This population-based study used data from the Korean National Health Insurance, a single mandatory health insurance system covering all residents. The uptake rates for screening for general health, gastric cancer, and colorectal cancer, which were provided by a national health screening program with free of charge or minimal cost in Korea from 2010-2020. Factors associated with general health, gastric cancer, and colorectal cancer screening were also explored. Results: Screening uptake rates for general health, gastric cancer, and colorectal cancer in PLWH increased from 2010-2019 but decreased in 2020. The standardized screening ratio showed lower screening rates for general health, gastric cancer, and colorectal cancer in PLWH with 0.80 (95 % confidence interval (CI) = 0.77-0.83), 0.64 (95 % CI = 0.61-0.67), and 0.67 (95 % CI = 0.64-0.71) in 2019. Increased age, Charlson Comorbidity Index, and years since HIV diagnosis were associated with increased screening uptake in PLWH. Otherwise, PLWH recipients of medical aid programs received less for each screening compared to PLWH who paid insurance premiums higher than 50 %. An increased medication possession ratio of highly active antiretroviral therapy was associated with decreased general health and gastric cancer screening uptake but increased colorectal cancer screening uptake. Conclusions: Significant disparities in health-screening uptake were observed in PLWH compared to the general population in a nationwide organized screening setting without cost barriers.